Clinical Fracture of Fiber Reinforced Resin Composite Versus Conventional Resin Composite Restorations in Endodontically Treated Molars: A Randomized Clinical Trial (Indian Journal of Public Health Research & Development, 2021)
Background: Short fiber reinforced resin composite (Ever X Posterior) is a bulk fill resin compositeindicated as a core dentine substitute at high stress-bearing areas improve strength and fracture toughness ofconventional resin composite and restored teeth. So, this randomized clinical trial was conducted to validateclinical performance of short fiber reinforced resin composite in endodontically treated molars.Method: 56 participants having endodontically treated lower molars with moderate amount of remainingtooth structure were randomly enrolled in this trial and received either Ever X Posterior covered by Gaenialposterior or only Gaenial posterior resin composite that applied according to manufacturer instructions.Mann-Whitney U test was used for intergroup comparisons and Wilcoxon signed rank test was used forintragroup comparisons. The significance level was set at p ? 0.05. No statistically significant difference wasobserved between both tested groups for all USPHS criteria at different follow-up periods except for colormatch favoring Gaenial posterior with a significant difference between both groups.Conclusion: Both types of restorations showed an acceptable clinical performance along 1 year follow-upperiod.
Keywords: Clinical fracture, Direct resin composite, Endodontically treated molars